Analysis of distributed power sources impact on distribution network voltage and reactive power optimization. Issue 2 (June 2020) - Di, Gai; Jiaolong, Lv; Yu, Su; Chuanbo, Liu; Yan, Li; Lishuai, He; Wenjia, Zhu; Yongquan, Tong; Boyu, Shi; Hui, Chen; Gang, Hou; Yuejun, Zhao
Abstract: The grid connection of distributed power sources will greatly change the initial electrical state of the system. Therefore, it is necessary to do scientific research on the impact of grid connection of distributed power sources and take appropriate measures to improve system stability. Two evaluation indexes of average voltage change rate and average voltage fluctuation rate are established to describe the impact of different distributed power grids on voltage. The IEEE 33-node power distribution network is used as a model. The distributed power source is connected to the power distribution network with different capacities and different locations. Based on the calculation results of the power flow, the voltage distribution diagrams of the system under different states are drawn, and a comprehensive analysis is performed according to the formulated quantitative indicators. A genetic algorithm was used to search for the optimal reactive power output of a single power supply connected to the grid.